TPS46, a Rice Terpene Synthase Conferring Natural Resistance to Bird Cherry-Oat Aphid, Rhopalosiphum padi (Linnaeus) - Sun, Yang; Huang, Xinzheng; Ning, Yuese; Jing, Weixia; Bruce, Toby J. A.; Qi, Fangjun; Xu, Qixia; Wu, Kongming; Zhang, Yongjun; Guo, Yuyuan (Frontiers in Plant Science, 2017)
ABSTRACT Plant terpene synthases (TPSs) are key enzymes responsible for terpene biosynthesis, and can play important roles in defense against herbivore attack. In rice, the protein sequence of TPS46 was most closely related to maize TPS10. However, unlike maize tps10, tps46 was also constitutively expressed in rice even in the absence of herbivore attack. Potential roles or constitutive emissions of specific volatiles may due to the constitutive expressions of tps46 in rice. Therefore, in the present study, RNA interference (Ri) and overexpression (Oe) rice lines were generated to investigate the potential function of TPS46 in Oryza sativa sp. japonica. Interestingly, the rice plants become more susceptible to Rhopalosiphum padi when expression of tps46 was silenced compared with Wt in greenhouse conditions. Artificial infestation bioassays further confirmed that Ri rice lines were susceptible to R. padi, whereas Oe rice lines were repellent to R. padi. Based on GC-MS and ToF-MS analysis, a total of eight volatile products catalyzed by TPS46 in rice were identified. Among them, only limonene and Eβf could be detected in all the Ri, Oe, and Wt lines, whereas other six volatiles were only found in the blend of volatiles from Oe lines. Moreover, the amount of constitutive limonene and Eβf in the Ri lines was significantly lower than in Wt lines, while the amounts of these two volatiles in the Oe line were obviously higher than in control rice. Our data suggested that the constitutive emissions of Eβf and limonene regulated by the constitutive expression of tps46 may play a crucial role in rice defense against R. padi. Consequently, tps46 could be a potential target gene to be employed for improving the resistance of plants to aphids.